O ensino de matemática da escola família agrícola de Goiás (EFAGO): um estudo de caso na perspectiva dos alunos e da professora do terceiro ano do ensino médio - Jesus, Carlos Augusto Cardoso de (2023)
This work aims to analyze the perceptions of a mathematics teacher and third year high school students about the sociocultural contributions of mathematics teaching at EFAGO, and how teaching is dialoguing with school documents. This concern arose from the perception of the peasants' need to use methodologies capable of promoting greater significance in their mathematical learning. For D'Ambrosio (1997) school education must combine theory and practice, therefore, teaching must have a deep connection with the sociocultural context of young people, mathematics resulting from this connection brings more meaning to students. Based on this objective, we question: does the teaching adopted at EFAGO dialogue with the sociocultural knowledge of the students and, consequently, makes the learning of mathematics meaningful? We understand this research as qualitative, being a case study. As data construction tools, we believe that the application of questionnaires and interviews, in addition to the construction of a field diary, enable data triangulation, which may increase the chances of success. To produce such contributions and reflections, we based ourselves on Begnami's (2019) theories on the pedagogy of alternation; mathematics teaching with Fiorentini (1995) and D'Ambrosio (1998), rural education with Caldart (2004), formal, non-formal and informal education with Gohn (2010).